2014
DOI: 10.1007/s00595-014-0867-7
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term outcomes of open inguinal hernia repair: comparison of the Prolene Hernia System and the Mesh Plug method

Abstract: The recurrence and wound infection rates were similar after hernia repair using the PHS and MP methods. Patients undergoing PHS repair developed fewer subcutaneous hematomas. An older age (≥65 years) was a significant independent risk factor for recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
0
11
1
Order By: Relevance
“…Recurrences can occur even 5 years after hernioplasty. 1 In the present study, other early and late postoperative complications were minor, and statistically significant differences between both groups could not be found. In order to rank the the Clavien-Dindo Classification was applied which consists of 5 grades.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Recurrences can occur even 5 years after hernioplasty. 1 In the present study, other early and late postoperative complications were minor, and statistically significant differences between both groups could not be found. In order to rank the the Clavien-Dindo Classification was applied which consists of 5 grades.…”
Section: Discussioncontrasting
confidence: 64%
“…This finding is compatible with the findings of other studies as Hayashi et al, Millikan et al and Gossetti et al studies. 1,8,13 Recurrence rate of the primary inguinal hernias after the introduction of mesh-based tensionless repairs has been reduced to approximately 1%.8 Several studies reported no significant difference was found in the recurrence rates between the laparoscopic and open mesh repairs. 10,15,19 Rutkow, and Robbins12 reported recurrence rate less than 1% after their MPR procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Study characteristics and outcome variables are presented in Table 1 . Most studies did not report the total number of hernias in women, but only the total number of female patients.…”
Section: Methodsmentioning
confidence: 99%
“…The literature describes laparoscopy as an effective approach, reducing cost of painkillers, intraoperative and long-term complications such as seroma, numbness, and pain [7][8][9] . Even with the most serious complications being rare, they are intestinal perforations and large vessel lesions.…”
Section: Introductionmentioning
confidence: 99%